Topological Solitons in High-order Nonlinear Material with Moiré Photonic Lattices - Luan, Nguyen Thanh; Dat, Ngo Trong; Thien, Nguyen Luong; Cuong, Duong Chinh; Anh Quan, Nguyen Duc; Tho, Do Duc; Viet Hung, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 41 No 1DO - 10.25073/2588-1124/vnumap.4965, 2025)
Moiré photonic lattices provide tunable geometric configurations that enable the formation and control of topological solitons. These solitons depend on the interplay between the underlying lattice geometry and high-order nonlinearities such as third and fifth-order effects. In this work, we employ Moiré lattices generated in a high-order nonlinear material to investigate the existence of topological solitons under diverse geometries, which are controlled by the twisting angle of sublattices. The formation of solitons in both commensurate and incommensurate Moiré lattice configurations allows us to explore deeper into the impact of geometric transitions on soliton stability and localization. The findings have potential applications in advanced photonic systems, including topological photonics and all-optical switching, where soliton stability and control are significant factors that can be optimized to enhance performance and functionality.